Phosphorylation of Ser711 residue in the hypervariable region of zoonotic genotype 3 hepatitis E virus is important for virus replication - Bo Wang; Sakthivel Subramaniam; Debin Tian; Hassan M. Mahsoub; C. Lynn Heffron; Xiang-Jin Meng (mBio)
ABSTRACT Hepatitis E virus (HEV) is distinct from other hepatotropic viruses because it is zoonotic. HEV-1 and HEV-2 exclusively infect humans, whereas HEV-3 and HEV-4 are zoonotic. However, the viral and/or host factors responsible for cross-species HEV transmission remain elusive. The hypervariable region (HVR) in HEV is extremely heterogenetic and is implicated in HEV adaptation. Here, we investigated the potential role of Serine phosphorylation in the HVR in HEV replication. We first analyzed HVR sequences across different HEV genotypes and identified a unique region at the N-terminus of the HVR, which is variable in the human-exclusive HEV genotypes but relatively conserved in zoonotic HEV genotypes. Using predictive tools, we identified four potential phosphorylation sites that are highly conserved in zoonotic HEV-3 and HEV-4 genomes but absent in human-exclusive HEV-1 strains. To explore the functional significance of these putative phosphorylation sites, we introduced mutations into the HEV-3 infectious clone and indicator replicon, replacing each Serine residue individually with alanine or aspartic acid, and assessed the impact of these substitutions on HEV-3 replication. We found that the phospho-blatant S711A mutant significantly reduced virus replication, whereas the phospho-mimetic S711D mutant modestly reduced virus replication. Conversely, mutations in the other three Serine residues did not significantly affect HEV-3 replication. Furthermore, we demonstrated that Ser711 phosphorylation did not alter host cell tropism of zoonotic HEV-3. In conclusion, our results showed that potential phosphorylation of the Ser711 residue significantly affects HEV-3 replication in vitro, providing new insights into the potential mechanisms of zoonotic HEV transmission.IMPORTANCEHEV is an important zoonotic pathogen, causing both acute and chronic hepatitis E and extrahepatic manifestation of diseases, such as neurological sequelae. The zoonotic HEV-3 is linked to chronic infection and neurological diseases. The specific viral and/or host factors facilitating cross-species HEV infection are unknown. The intrinsically disordered HVR in ORF1 is crucial for viral fitness and adaptation, both in vitro and in vivo. We hypothesized that phosphorylation of Serine residues in the HVR of zoonotic HEV by unknown host cellular kinases is associated with cross-species HEV transmission. In this study, we identified a conserved region within the HVR of zoonotic HEV strains but absent in the human-exclusive HEV-1 and HEV-2. We elucidated the important role of phosphorylation at the Ser711 residue in zoonotic HEV-3 replication, without altering the host cell tropism. These findings contribute to our understanding the mechanisms of cross-species HEV transmission.